A Perspective of the Comprehensive and Objective Assessment of Analytical Methods Including the Greenness and Functionality Criteria: Application to the Determination of Zinc in Aqueous Samples - Nowak, Paweł Mateusz; Wietecha-Posłuszny, Renata; Woźniakiewicz, Michał; Woźniakiewicz, Aneta; Król, Małgorzata; Kozak, Joanna; Wieczorek, Marcin; Knihnicki, Paweł; Paluch, Justyna; Telk, Anna; Mermer, Karolina; Kochana, Jolanta; et al. (Frontiers in Chemistry, 2021)
The recently proposed concept of White Analytical Chemistry (WAC), referring to the Red-Green-Blue color model, combines ecological aspects (green) with functionality (red and blue criteria), presenting the complete method as "white". However, it is not easy to carry out an overall quantitative evaluation of the analytical method in line with the WAC idea in an objective manner. This paper outlines the perspective of the future development of such a possibility by attempting to answer selected questions about the evaluation process. Based on the study consisting in the evaluation of selected model methods by a group of 12 independent analysts, it was shown how well individual criteria are assessed, whether the variability of assessments by different people is comparable for each criterion, how large it is, and whether averaging the scores from different researchers can help to choose the best method more objectively.